Practice-Oriented Teaching in Preparing Future Teachers-Psychologists for Professional Activity - Manashova, Gulmira N.; Shkutina, Larissa A.; Mirza, Natalya V.; Beisenbekova, Gulmira B.; Jabayeva, Gulden N. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
In this article, devoted to the problem of professional training of future teachers-psychologists based on practice-oriented teaching, the research results, tested during the educational process, are presented. They are as follows: the essence of the concept "professional competence" of a teacher is specified; based on the analysis of existing approaches to the study of the structure of professional readiness, personal, intellectual-operational, motivational, communicative, and reflexive components are determined; the structural and functional model of practice-oriented teaching of future teachers-psychologists has been developed following the pedagogical features of practice-oriented teaching and the identified pedagogical conditions, which includes four interrelated blocks: the target, the methodological, the content-procedural, the learning outcome. The criteria of professional training of future teachers-psychologists on the basis of practice-oriented teaching (personal, intellectual-operational, motivational, communicative, and reflexive) and levels of readiness are defined: reproductive (low), adaptive (medium), and integrative (high). The development and consolidation of skills in students is carried out by solving specific tasks of professional activity, during which students try to explain the procedure for solving a specific professional task and check the actual material in practice. The practice-oriented content of the educational material allows bringing teaching closer to specific situations of professional activity, the chosen specialty, to form the life experience of students, thus increasing the level of knowledge and skills, cognitive interest, and, as a result, to form the level of professional competence of students.